Behavior of Historic Buildings in Zones with Moderate Seismic Activity. Case Study: Banat Region, Romania. (2016) - Narita, Alina; Mosoarca, Marius; Modena, Claudio; da Porto, Francesca; Munari, Marco; Taffarel, Sabrina; Marson, Claudia; Valotto, Claudia; Roverato, Margherita
Abstract: Historic buildings from seismic zones have recorded important damages after earthquakes. Due to this aspect, in current design codes for consolidations of some countries there are special calculations for historic buildings. The development of the investigation methods for the damages developed in the historic bearing structures revealed the fact that these damages are differentiated by the type and intensity of the earthquake. Information on these different failure modes of the historic bearing structures is not given in the current design codes for zones with medium and reduced seismic activity. In Romania there are no specific provisions for the design of the consolidation works of historic bearing structures, even though there are two important seismic zones: Vrancea region and Banat region. The Vrancea region is characterized by deep earthquakes while the Banat region is characterized by shallow earthquakes. These two types of earthquakes produce different failure modes for similar historic buildings. In this article there are presented specific failure modes of historic buildings such as orthodox churches, catholic churches, synagogues, residential buildings, and aggregate buildings from Banat region which has moderate seismic activity. The evaluation methodology of the seismic vulnerability of buildings from historic centers developed by the University of Padova was confirmed by in situ identification of failure mechanisms recorded in historic bearing structures from Timisoara. There are also presented specific recommendations regarding the design philosophy of the consolidations for zones with moderate seismic activity, by the control of the fundamental requirements for buildings: rigidity and ductility.